Présentations de Londres : Ackroyd, Moorcock, Sinclair et l’éthique de l’adjacence - Jean-Michel Ganteau (Anglophonia)
This article focuses on three contemporary novels that are emblematic of the canon of the contemporary London novel: Peter Ackroyd’s Hawksmoor, Michael Moorcock’s Mother London and Iain Sinclair’s White Chappell, Scarlet Tracings. Its theoretical concern is with the figures of adjacency as evinced in the corpus which promotes layering and fragmentation and, whose purpose seems to fragment the better to relate. More specifically, taking its lead from Agamben, it concentrates on the interstices between the fragments which are the figures of adjacency proper as they allow for the irruption of a visionary presentation not incompatible with the workings of a negative presentation of the sublime type. In the end, despite their semiotically saturated, simulation prone surfaces, those texts accommodate the possibility of epiphany. One step further, they favour a vision of adjacency as a figure of proximity and exteriority, in the Levinasian meaning of the term, hence a heterological vision of the city.